Part 1
The probability that a man who likes carrots is a meat eater
"=(\\frac{80}{100} \\times \\frac{60}{100}) \\times (\\frac{20}{100}\\times \\frac{80}{100})\\\\\n=\\left(\\frac{4}{5}\\times \\frac{3}{5}\\right)\\times \\left(\\frac{20}{100}\\times \\frac{4}{5}\\right)\\\\\n=\\frac{12}{25}\\times \\frac{4}{25}\\\\\n=\\frac{48}{625}"
Part 2
Back-up Theory
If A and B are independent, P(A and B) = P(A ∩ B) = P(A) x P(B) ..……….....................…(1)
Now to work out the solution,
Given,
X = number of tosses until one of the two coins turns up a head and the other a tail.
P(the first coin turns up head) = 0.74 ....................................................................................... (2)
P(the second coin turns up head) = 0.12 ................................................................................. (3)
The pay-off at the end of the game: G(X) = X2 + 2 ....................................................................(4)
All tosses are independent. ................................................................................................ (5)
We want:
"P[G(X) > 6]\\\\\n\n= P[X2 + 2 > 6] [vide (4)]\\\\\n\n= P[X2 > 4]\\\\\n\n= P(X > 2) [note X2 > 4 => X > 2 or X < - 2; but then X cannot be negative]\\\\\n= 1 \u2013 P(X \u2264 2)\\\\\n\n= 1 \u2013 P(X = 2)"
[‘one of the two coins turns up ahead and the other a tail’ => minimum value of X is 2 ]
= 1 – [P{(the first coin turns up head and the second coin turns up tail)}
+ P{(the first coin turns up tail and the second coin turns up head)}]
= 1 – {(0.74 x 0.88) + ((0.26 x 0.12))} [vide (5), (1), (2) and (3)]
= 1 – 0.6824
= 0.3176
Part 3
"\\frac{\\partial \\:}{\\partial \\:x}\\left(x^9y^6\\right)=9x^8y^6\\\\\n\\frac{\\partial \\:}{\\partial \\:y}\\left(x^9y^6\\right)=6x^9y^5"
Part 4
"=> GCD(493, 899 - 493) = GCD(493, 406)\\\\\n=> GCD(493 - 406, 406) = GCD(87, 406)\\\\\n=> GCD(87, 406 - 87) = GCD(87, 319)\\\\\n=> GCD(87, 319 - 87) = GCD(87, 232)\\\\\n=> GCD(87, 232 - 87) = GCD(87, 145)\\\\\n=> GCD(87, 145 - 87) = GCD(87, 58)\\\\\n=> GCD(87 - 58, 58) = GCD(29, 58)\\\\\n=> GCD(29, 58 - 29) = GCD(29, 29)\\\\\n=> GCD(29, 29 - 29) = GCD(29, 0)\\\\\nGCD(29, 0) is 29"
Comments
Leave a comment